2021
DOI: 10.1002/cpt.2237
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Clinical Pharmacology to HIV Cure Research

Abstract: AdherenceLow drug concentrations and low ART adherence, predicted future viremia in PLWH, as measured by quantitation of tenofovir-diphosphate in dried blood spots. Viral blips and low-level viremia are associated with a larger reservoir size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 101 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…In people with chronic HIV, ART intensification with addition of a single agent, frequently raltegravir, has largely, but not uniformly, been shown to not reduce residual viremia or reservoir size [7,8]. Importantly, tissue reservoirs for HIV may also be pharmacologic sanctuaries for antiretroviral drugs [9]. Therefore, intensification strategies must actually enhance anti-HIV activity at the tissue source of residual viremia, which was not demonstrated.…”
mentioning
confidence: 99%
“…In people with chronic HIV, ART intensification with addition of a single agent, frequently raltegravir, has largely, but not uniformly, been shown to not reduce residual viremia or reservoir size [7,8]. Importantly, tissue reservoirs for HIV may also be pharmacologic sanctuaries for antiretroviral drugs [9]. Therefore, intensification strategies must actually enhance anti-HIV activity at the tissue source of residual viremia, which was not demonstrated.…”
mentioning
confidence: 99%
“…Finally, our group has provided a proof-of-concept that Vδ2 T cells may be incorporated into current strategies for HIV cure within virally suppressed people living with HIV [ 71 , 72 ]. One approach utilized in HIV cure strategies encompasses reactivation of latent virus using small compounds generally called latency reversing agents and boosting immune responses [ 73 , 74 , 75 , 76 , 77 , 78 ]. We demonstrated that autologous expanded Vδ2 T cells mediated killing of latently HIV-infected CD4+ T cell reservoirs upon reactivation.…”
Section: Clinical Applications Of Vδ2 T Cell Immunotherapymentioning
confidence: 99%
“…3233 Additionally, strategies to cure HIV are complicated in part by pharmacological challenges (eg, limited drug distribution at effector sites such as in tissues, inadequate therapeutic efficacy, and unfavorable drug toxicity). 3435…”
Section: Introductionmentioning
confidence: 99%